2016
DOI: 10.1128/aem.02881-15
|View full text |Cite
|
Sign up to set email alerts
|

N -Glycosylation Improves the Pepsin Resistance of Histidine Acid Phosphatase Phytases by Enhancing Their Stability at Acidic pHs and Reducing Pepsin's Accessibility to Its Cleavage Sites

Abstract: N-Glycosylation can modulate enzyme structure and function. In this study, we identified two pepsin-resistant histidine acid phosphatase (HAP) phytases from Yersinia kristensenii (YkAPPA) and Yersinia rohdei (YrAPPA), each having an N-glycosylation motif, and one pepsin-sensitive HAP phytase from Yersinia enterocolitica (YeAPPA) that lacked an N-glycosylation site. Site-directed mutagenesis was employed to construct mutants by altering the N-glycosylation status of each enzyme, and the mutant and wild-type enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 55 publications
1
21
0
1
Order By: Relevance
“…On the other hand, for drugs that treat chronic conditions, the absence of glycosylation is desired to avoid effector functions and associated inflammatory responses. Another important consideration is that glycosylated proteins are less susceptible to proteases, such as pepsin, compared with aglycosylated counterparts (Niu et al, 2016), which should be considered to maximize protein yield.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for drugs that treat chronic conditions, the absence of glycosylation is desired to avoid effector functions and associated inflammatory responses. Another important consideration is that glycosylated proteins are less susceptible to proteases, such as pepsin, compared with aglycosylated counterparts (Niu et al, 2016), which should be considered to maximize protein yield.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, Y. kristensenii YkAPPA and Y. enterocolitica YeAPPA were sensitive to pepsin after expression in E. coli , but E. coli -produced Y. rohdei YrAPPA was highly pepsin-resistant 21 30 36 37 . In this study, we employed a structure-based rational design approach to engineer a residual side chain in the surface pepsin cleavage site of Yersinia phytases to increase enzyme performance.…”
mentioning
confidence: 91%
“…The surface positive charge of Photinus pyralis firefly luciferase was reduced to generate a mutant enzyme with an increased trypsin digestion half-life of about 4-fold at 23 °C 29 . Site-directed mutagenesis demonstrated that the N -glycosylation conferred pepsin resistance on Yersinia phytases and stability at acidic pH 30 . Other engineered phytase mutants also showed increased resistance to proteolysis and improved thermostability 31 32 33 .…”
mentioning
confidence: 99%
“…The effect of mucins on peptides activity was evaluated by MIC and by time killing assay as explained below. The resistance of the peptides to pepsin was tested as previously described with some changes [28]. Briefly, temporin-SHa and its analogs (at 1 mg/mL, final concentration) were incubated for 4 h at 37 °C with 1 mg/mL (final concentration) of pepsin from porcine gastric mucosa (Sigma-Aldrich) in HCl 10mM, pH 2.…”
Section: Methodsmentioning
confidence: 99%